Kepatuhan konsumsi suplemen mikronutrien tidak terpengaruh oleh bentuk suplemen - Faurina Risca Fauzia; Arta Farmawati; Lily Arsanti Lestari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Compliance of micronutrients supplement consumption was not affected by supplements formBackground: Taburia is micronutrient sprinkle produced by Ministry of Health Indonesia to overcome malnutrition problem in Indonesia. Compliance of Taburia consumption is an important indicator for the success of the supplementation program. Taburia’s compliance in some regions is low (<80%). Gummy candies are children’s favorable food product.Objective: To evaluate the compliance of micronutrient consumption in the form of sprinkle and gummy candies in children. Methods: This study was a quasi-experimental study with randomizedcontrol group design.Respondents are mother and children aged 36-59 months in Yogyakarta District. The children received supplementation of Taburia sprinkle or fortified gummy candies for 30 days.Results: The compliance of Taburia sprinkle and fortified gummy candies were 85.39% and 80.32% respectively, however it was not significantly different (p>0.05). Several factors affected the compliance level such as mother’s employment status, gender of the children, and age of the children. Conclusions: The compliance level of Taburia sprinkle and fortified gummy candies was similar. Hence fortified gummy candies could be used as an alternative of micronutrient supplement to overcome nutrition problem in Indonesia.